2010
DOI: 10.1051/0004-6361/201014800
|View full text |Cite
|
Sign up to set email alerts
|

High-order aberration compensation with multi-frame blind deconvolution and phase diversity image restoration techniques

Abstract: Context. For accurately measuring intensities and determining magnetic field strengths of small-scale solar (magnetic) structure, knowledge of and compensation for the point spread function is crucial. For images recorded with the Swedish 1-meter Solar Telescope (SST), restoration with multi-frame blind deconvolution (MFBD) and joint phase diverse speckle (JPDS) methods lead to remarkable improvements in image quality but granulation contrasts that are too low, indicating additional stray light. Aims. We propo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
3
41
1
Order By: Relevance
“…This happens because the PD error metric does not optimize the WF, but the image quality. A similar phenomenon has been reported by [4,31]: PD can find better reconstructions compared to what is obtained when the deconvolution is done using a perfect modal WF representation being truncated to as many coefficients. Here, we observe a variation of the same effect.…”
Section: Performance On Realistic Ao Datasupporting
confidence: 84%
“…This happens because the PD error metric does not optimize the WF, but the image quality. A similar phenomenon has been reported by [4,31]: PD can find better reconstructions compared to what is obtained when the deconvolution is done using a perfect modal WF representation being truncated to as many coefficients. Here, we observe a variation of the same effect.…”
Section: Performance On Realistic Ao Datasupporting
confidence: 84%
“…This has now been resolved by measurements of the point spread function (PSF) in the Solar Optical Telescope (SOT) on the Hinode spacecraft (Wedemeyer-Böhm 2008) and comparison with artificial data (Wedemeyer-Böhm & Rouppe van der Voort 2009). Scharmer et al (2010, see their introduction for a full account of the problem) recently initiated a project to measure the straylight sources of the Swedish 1-meter Solar Telescope (SST; Scharmer et al 2003a) to also correct SST images for the missing contrast. Scharmer et al (2010) found that a significant part of the contrast reduction can be explained by high-order modes in the pupil wavefront phase that are not corrected by the Adaptive Optics (AO; Scharmer et al 2003b) or image restorations with multi-frame blind deconvolution (MFBD; Löfdahl 2002) techniques because of the finite number of modes used in those techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Scharmer et al (2010, see their introduction for a full account of the problem) recently initiated a project to measure the straylight sources of the Swedish 1-meter Solar Telescope (SST; Scharmer et al 2003a) to also correct SST images for the missing contrast. Scharmer et al (2010) found that a significant part of the contrast reduction can be explained by high-order modes in the pupil wavefront phase that are not corrected by the Adaptive Optics (AO; Scharmer et al 2003b) or image restorations with multi-frame blind deconvolution (MFBD; Löfdahl 2002) techniques because of the finite number of modes used in those techniques. The authors also implemented a method for correcting the contrast by means of the known statistics of atmospheric turbulence and simultaneous measurements of Fried's parameter r 0 from a wide-field wavefront sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The contrasts in Table 1 are much lower than those in Fig. 9 because of various sources of stray light, see discussion by Scharmer et al (2010). The contrasts show the expected increase in contrast with S tilt compensation, more for large θ than for small.…”
mentioning
confidence: 70%